Health literacy and its association with adherence in pediatric liver transplant recipients and their parents. (14th May 2020) - Dore‐Stites, Dawn; Lopez, M. James; Magee, John C.; Bucuvalas, John; Campbell, Kathleen; Shieck, Victoria; Well, Andrew; Fredericks, Emily M.
Abstract: Objective: Non‐adherence to pediatric regimens is a common concern. Low health literacy is correlated with poor outcomes in adults but is understudied in pediatrics. The current project aimed to determine the relationship between health literacy, adherence, and outcomes in pediatric liver transplant recipients. Hypotheses included a) parent and patient health literacy would be positively correlated; and b) low patient and/or parent health literacy would be negatively correlated with adherence and health outcomes. Patients and Methods: Eligible participants were recruited during routine follow‐up visits in a pediatric liver transplant clinic. Parents and patients (>13 years old) completed 2 measures of health literacy. Patients ≥18 years completed health literacy measures without corresponding parent surveys. Adherence variables and health outcomes were obtained from medical records. Results: Seventy‐nine patients across two sites completed the study. Variance in classification of health literacy between measures was observed; however, most parents (82%‐100%) scored within an "adequate literacy" range. More adolescents scored in lower health literacy ranges relative to the parents. Markers of SES were positively correlated with health literacy. Parent health literacy was negatively associated with biopsy‐proven rejection episodes and the number of hospitalizations; however, it was not associated with measures of tacrolimus adherence. There were no relationships observed between parent and adolescent health literacy. Conclusions: Health literacy is an important consideration in managing patient care; however, available measures demonstrate variability in capturing the skills of patients. Effective communication strategies may ameliorate admittedly small, but negative, impacts of limited health literacy on outcomes.